مزايا قانون الاستثمار رقم 22-18 وتأثيرها على مناخ الأعمال في الجزائر - غربي ،سليم; عين ،فتحي; إسماعيل ،جوادي (جامعة الوادي University of El Oued, 2024)
بعد توجّه البلاد من الاقتصاد الموجّه إلى الاقتصاد الحرّ، سنّ المشرّع جملة من القوانين بغية تحسين المناخ الاستثماري كالمرسوم التشريعي 93 – 12، ثمّ الأمر 01 – 03 مرورا بالقانون 16 - 09 وانتهاء بالقانون الجديد 22 – 18 ، وهذه النّصوص جاءت لتساهم في الدفع بعجلة الاستثمار للنهوض بالاقتصاد الوطني، ونظرا لمبدأ حرية الاستثمار الّذي كرّسه دستور 2020 في المادة 61 منه، وأمام الاختلالات في توزيع الاستثمارات على مستوى القطاعات، وكذا على مستوى المناطق ، ما دفع المشرّع بمحاولة جلب الاستثمار وتوجيهه لمواطن الاختلال وذلك لإحداث الرقي والتوازن المنشود، وذلك عبر جملة من المزايا في شكل إغراءات وتحفيزات. After the country's orientation towards a free economy, the legislature enacted a number of laws to improve the investment climate such as Legislative Decree 93-12, then Ordinance 01-03 through Law 16 - 09 and the end of the new law 22 - 18, these provisions have contributed to the acceleration of investment for the advancement of the national economy; Given the principle of freedom of investment enshrined in article 61 of the 2020 Constitution and the imbalances in the distribution of investments at the sector level, At the regional level, the legislator's attempt to attract and direct investment to the disadvantaged is prompted by a number of advantages in the form of inducements and incentives.
ماستر اعمال